INOVASI BUDAYA ORGANISASI DI SEKTOR PUBLIK: STRATEGI ADAPTASI TERHADAP DISRUPSI DIGITAL - Hanifah, Zarma; Frinaldi, Aldri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The rapid development of digital technology has had a significant impact on the public sector, including the bureaucratic service system in Indonesia. Digital disruption demands that public organizations adapt by transforming their organizational culture into one that is more flexible, innovative, and collaborative. However, the organizational culture of Indonesian bureaucracy remains dominated by hierarchical and procedural values, which serve as obstacles in the digitalization of public services. This article aims to analyze the current conditions of organizational culture in Indonesia’s public sector amid digital disruption, identify the challenges faced in transforming organizational culture, and formulate adaptive innovation strategies for digital environments. This study employs a descriptive-qualitative approach through a literature review of relevant scholarly journals, books, government policy reports, and prior research findings. The results indicate that the main challenges in transforming organizational culture within the public sector include employee resistance to technological change, limited digital competencies among civil servants, unadaptive bureaucratic leadership, rigid work culture, and a lack of incentives for innovation. Recommended strategies include strengthening digital leadership, developing a digital mindset, redefining organizational values, digitalizing work practices, and applying the Competing Values Framework (CVF) to guide structured and measurable cultural transformation. Digital-based organizational culture transformation is a strategic necessity to realize a modern, adaptive, and service-oriented public bureaucracy in Indonesia. ABSTRAKPerkembangan teknologi digital telah membawa dampak signifikan terhadap sektor publik, termasuk dalam sistem pelayanan birokrasi di Indonesia. Disrupsi digital menuntut organisasi publik untuk beradaptasi melalui transformasi budaya kerja yang lebih fleksibel, inovatif, dan kolaboratif. Namun demikian, budaya organisasi birokrasi Indonesia masih didominasi nilai-nilai hierarkis dan prosedural yang menjadi hambatan dalam proses digitalisasi pelayanan publik. Artikel ini bertujuan untuk menganalisis kondisi budaya organisasi sektor publik Indonesia dalam menghadapi era disrupsi digital, mengidentifikasi tantangan yang dihadapi dalam transformasi budaya organisasi, serta merumuskan strategi inovasi budaya organisasi yang adaptif terhadap lingkungan digital. Metode yang digunakan adalah deskriptif-kualitatif melalui studi literatur dari berbagai jurnal ilmiah, buku, laporan kebijakan pemerintah, dan hasil penelitian terkait. Hasil kajian menunjukkan bahwa tantangan utama transformasi budaya organisasi di sektor publik meliputi resistensi pegawai terhadap teknologi, rendahnya kompetensi digital ASN, kepemimpinan birokrasi yang belum adaptif, budaya kerja yang kaku, dan minimnya insentif bagi inovasi. Strategi yang direkomendasikan meliputi penguatan kepemimpinan digital, pengembangan digital mindset, redefinisi nilai-nilai organisasi, digitalisasi praktik kerja, serta penerapan model Competing Values Framework (CVF) untuk perubahan budaya yang terukur. Transformasi budaya organisasi berbasis digital menjadi keharusan strategis untuk mewujudkan birokrasi Indonesia yang modern, adaptif, dan berorientasi pelayanan publik berkualitas.